O1 Efficacy and safety of endoscopic submucosal dissection of early gastric neoplasia in the West: a multicentre prospective european study. (19th June 2022) - Abdelrahim, Mohamed; Alkandari, Asma A; Galtieri, Piera Alessia; Spadaccini, Marco; Groth, Stefan; Pilonis, Nastazja D; Subhramaniam, Sharmila; Kandiah, Kesavan; Hossain, Ejaz; Invernizzi, Martina; Kaminski, Michal F; Seewald, Stefan; et al.
Abstract : Introduction: Endoscopic submucosal dissection is considered the first line treatment for early gastric neoplasia, and extensive data is reported from the Far East demonstrating its efficacy and safety even in expanded criteria in the Japanese guidelines. Data from the west is still limited to mostly small series from single centres. In this study, we describe a large multicentre, European cohort and review outcome and safety of gastric ESD in the hands of western experts in the light of the latest Japanese indication criteria. Methods: This is a prospective observational cohort study conducted in four large endoscopy referral centres in four European countries. Study included patients referred for gastric ESD in participating centres in the period from 2009 to 2020. Data was prospectively collected on patient demographics, lesion characteristics, procedure details and outcomes of endoscopic treatment. Indications for endoscopic resection were categorised according to the latest Japanese guidelines. Patients were followed up clinically and endoscopically as per standard protocols. Statistical analysis using logistic regression was performed. Results: A total of 340 patients were included. Mean age was 72 years and 55.6% were males. Absolute criteria were fulfilled in 74.4% of patients. Median follow up duration was 39 months. Post resection histology was adenocarcinoma, HGD, LGD and other in 52.5%, 20.7%, 16.8% and 10.0% respectively. Poor differentiation was reported in 14.6% of adenocarcinoma. Early bleeding, delayed bleeding and perforation occurred in 5.3%, 3.2% and 2.1% respectively. En bloc, R0 and recurrence rates were 93.8%, 82.9% and 6.7%. Relative indication was independently associated with R1 outcome (OR 3.90, 95% CI 1.64, 9.24, P value 0.002). Table (1) below summarises the outcomes and complications. Conclusion: This is the largest, multicentre, European cohort suggesting ESD is safe and effective treatment of early gastric neoplasia in the western setting. Our data suggests the Japanese expanded and relative criteria for gastric ESD may be safe in the western practice; however more data is needed to fully characterise this group and inform future selection and surveillance guidelines.